Textual Input Enhancement for Vowel Blindness: A Study with Arabic ESL Learners. Issue 1 (March 2015) - Alsadoon, Reem; Heift, Trude
<x xml:space="preserve">Abstract</x> This study explores the impact of textual input enhancement on the noticing and intake of English vowels by Arabic L2 learners of English. Arabic L1 speakers are known to experience vowel blindness, commonly defined as a difficulty in the textual decoding and encoding of English vowels due to an insufficient decoding of the word form. Thirty beginner ESL learners participated in a training study during which the experimental group received textual input enhancement on English vowels. Students completed a pretest and an immediate and delayed posttest. An eye‐tracker recorded students' eye fixations during the treatment phase. Results indicate that vowel blindness was significantly reduced for the experimental group who received vowel training in the form of textual input enhancement. This might be due to a longer focus on the target words as suggested by our eye‐tracking data.